Euroskepticism, income inequality and financial expectations - Ritzen, Jo [Verfasser]; Wehner, Caroline [Verfasser]; Zimmermann, Klaus F. [Verfasser] (My University, 2016)
“Before the Great Recession, the rising income inequality within the “old” European Union has been suggested as an important driver of the increase in Euroskepticism. We revisit this finding for the 27 EU member states from 2006 to 2011, introducing individual negative financial expectations as a further driving factor. We also distinguish between Western and Eastern European countries. In the period of Eastern EU enlargement after 2005, Euroskepticism increased by one third while income inequality on average remained stable. Negative financial expectations are positively related to Euroskepticism in the West and non-significantly negatively related in the East. This suggests that Westerners interpret European integration as a threat, while Easterners view it as a chance. In addition, income inequality lost its role in “old” Europe. An increase of one Gini point decreases the probability of Euroskepticism by half a percentage point in the West, while it has no impact in the East.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; I 2.2 Europa; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; 370; 330; Europäische Union; Einkommenshöhe; Einkommensunterschied; Einkommensentwicklung; Erwartung; Westeuropa; Osteuropa; Quantitative Angaben